Three New Abietane‐type Diterpenes from the Bark of Cryptomeria japonica. Issue 9 (14th September 2016) - Chang, Chi‐I; Chen, Chien‐Chih; Wang, Sheng‐Yang; Chao, Che‐Yi; Chao, Louis Kuoping; Chen, Jih‐Jung; Ko, Horng‐Huey; Chen, Cheng‐Chi; Kuo, Yueh‐Hsiung
Abstract : Abstract : Three new abietane‐type diterpenoids, 7 β ‐acetoxy‐12‐methoxyabieta‐8, 11, 13‐triene‐6 α, 11‐diol (1 ), 7 α ‐acetoxy‐12‐methoxyabieta‐8, 11, 13‐triene‐6 α, 11‐diol (2 ), and 6 α ‐acetoxy‐12‐methoxyabieta‐8, 11, 13‐triene‐7 α, 11‐diol (3 ), as well as two known abietane‐type diterpenoids, 12‐methoxyabieta‐8, 11, 13‐triene‐6 α, 7 β, 11‐triol (4 ) and 6 α ‐acetoxy‐12‐methoxyabieta‐8, 11, 13‐triene‐7 β, 11‐diol (5 ), were isolated from the MeOH extract of the bark of Cryptomeria japonica . Their structures were determined by analysis of spectroscopic data and comparison of NMR data with those of related metabolites.